Simple and efficient methods for enrichment and isolation of endonuclease modified cells. - Branden S Moriarity (Public Library of Science (PLoS), 2014)
The advent of Transcription Activator-Like Effector Nucleases (TALENs), and similar technologies such as CRISPR, provide a straightforward and cost effective option for targeted gene knockout (KO). Yet, there is still a need for methods that allow for enrichment and isolation of modified cells for genetic studies and therapeutics based on gene modified human cells. We have developed and validated two methods for simple enrichment and isolation of single or multiplex gene KO's in transformed, immortalized, and human progenitor cells. These methods rely on selection of a phenotypic change such as resistance to a particular drug or ability to grow in a selective environment. The first method, termed co-transposition, utilizes integration of a piggyBac transposon vector encoding a drug resistance gene. The second method, termed co-targeting, utilizes TALENs to KO any gene that when lost induces a selectable phenotype. Using these methods we also show removal of entire genes and demonstrate that TALENs function in human CD34+ progenitor cells. Further, co-transposition can be used to generate conditional KO cell lines utilizing an inducible cDNA rescue transposon vector. These methods allow for robust enrichment and isolation of KO cells in a rapid and efficient manner.